2013
DOI: 10.3747/co.20.1630
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cost for Initial Management of Prostate Cancer: A Systematic Review

Abstract: Background: Prostate cancer (pca) is the most common non-skin cancer among men in Canada and other Western countries. Increased prevalence and higher cost of newer treatments have led to a significant rise in the economic burden of pca. The objectives of the present study were to systematically review the literature on direct costs for the initial management of pca, and to examine the methodologic considerations across studies. Methods: Bibliographic databases were systematically searched for peer-reviewed art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
10
0
3
Order By: Relevance
“…Most of the studies produced a mean cost for their study sample and estimated an average cost ranging from US$13,000 3 to US$18,000 2,4,7 for the initial care for prostate cancer. Also consistent with other studies, the results of our analysis showed that the Medicare costs varied with the choice of initial treatment . The costs attributable to prostate cancer were lower for patients who received watchful waiting and higher for patients who underwent ADT or radical prostatectomy …”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies produced a mean cost for their study sample and estimated an average cost ranging from US$13,000 3 to US$18,000 2,4,7 for the initial care for prostate cancer. Also consistent with other studies, the results of our analysis showed that the Medicare costs varied with the choice of initial treatment . The costs attributable to prostate cancer were lower for patients who received watchful waiting and higher for patients who underwent ADT or radical prostatectomy …”
Section: Discussionsupporting
confidence: 90%
“…in our study, the analysis captured health care resource utilisation and direct costs both in the primary and specialist care settings, assessed productivity costs due to disease and also informal care given by family members or relatives and friends. Many studies in this area have focused on direct health care costs only [13], although there have been some attempts to assess productivity costs also in the cancer setting [5,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it imposes a substantial burden of illness, which is expected to increase with an aging population and a rising frequency of diagnosis . Once prostate cancer has metastasized, the disease is especially deadly and costly …”
Section: Introductionmentioning
confidence: 99%
“…2 Once prostate cancer has metastasized, the disease is especially deadly and costly. 3 The management of metastatic prostate cancer is categorized by 2 phases: while the disease is initially sensitive to androgen deprivation therapy (ADT; ie, castration-sensitive or castration-naive) and after it becomes resistant to ADT (ie, castration-resistant). 4 For metastatic hormone-sensitive prostate cancer, the current treatment landscape is changing, although ADT remains a cornerstone therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation